Extramedullary relapse of acute myelogenous leukaemia due to chronic GVHD as a complication of allogeneic HSCT - Nasilowska-Adamska, Barbara; Tomaszewska, Agnieszka; Halaburda, Kazimierz; Prochorec-Sobieszek, Monika; Strzelczyk, Piotr; Wierzbowska, Agnieszka; Smolarczyk-Wodzynska, Justyna; Pieńkowska-Grela, Barbara; Marianska, Bozena (Archives of Medical Science, 2009)
We report a 41-year-old man with AML and unfavourable complex chromosome abnormalities who was treated with alloHSCT in first complete remission. Two years after transplant due to limited chronic GVHD this patient presented painful oedema around the left wrist. Histology of the soft tissue tumour, found in CT scanning of this wrist, revealed isolated extramedullary (EM) leukaemia relapse. He was treated with surgery, local radiotherapy and systemic chemotherapy. This case suggests that the anti-leukaemic effect of GVHD in EM sites might not be effective. Moreover, there is a possibility that GVHD predisposes to isolated EM relapses of leukaemia.